2012
DOI: 10.1021/ef300275e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphorus on Alkali Distribution during Combustion of Logging Residues and Wheat Straw in a Bench-Scale Fluidized Bed

Abstract: The influence of phosphorus on the alkali distribution in fluidized (quartz) bed combustion using two different typical biomasses (logging residues and wheat straw) was studied. Phosphoric acid (H 3 PO 4 ) was used as an additive. The produced ash fractions were analyzed for morphology and elemental composition by scanning electron microscopy-energy-dispersive spectroscopy (SEM-EDS), and crystalline phases by powder X-ray diffraction (P-XRD). For both fuel assortments tested, a reduction of volatilized deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 37 publications
5
88
0
Order By: Relevance
“…Major elements were found in larger amounts using SEM-EDS, which is possibly derived from the precision and accuracy of the techniques. Infrared absorption spectroscopy is used primarily to identify organic compounds, especially gases [3,4,19,22]. FTIR is not typically used for the determination of inorganic compounds, as these components vibrate at wavenumbers less than 400 cm −1…”
Section: Comparison Between Elemental Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Major elements were found in larger amounts using SEM-EDS, which is possibly derived from the precision and accuracy of the techniques. Infrared absorption spectroscopy is used primarily to identify organic compounds, especially gases [3,4,19,22]. FTIR is not typically used for the determination of inorganic compounds, as these components vibrate at wavenumbers less than 400 cm −1…”
Section: Comparison Between Elemental Techniquesmentioning
confidence: 99%
“…However, biomass, as a solid fuel, generates a significant amount of ash. Some of the ash is retained in the boiler grate as bottom ash, some is released in the flue gas as fly ash and, the remaining amount forms deposits in the internal parts of the boiler, causing problems such as fouling, slagging and corrosion among others [2][3][4][5][6]. Fouling is defined as deposits that form in areas of the boiler that are subjected to convective heat exchange.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the rate of alkali chloride sulfation increased, and more HCl was released in the flue gas. Grimm et al 48 showed that the addition of phosphorus to biomass changed the system from being dominated by amorphous alkali-silicate ash fractions and fine particulate alkali chlorides to a system dominated by crystalline coarse ash of alkali-Ca/Mg-phosphates and fine particulates of alkali sulfates.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Co-combustion of MSS with other types of waste streams or biomass may increase the solubility of the phosphates formed and thereby increase the potential for phosphorus recovery from the ash produced in combustion. 5,13,[18][19][20][21] The impact on alkali capture from the increased sulphur content in the fuel blends can be seen in table 3. Both arkanite (K 2 SO 4 ) and aphtitalite (K 3 Na(SO 4 ) 2 ) were observed in considerable amounts for the cocombustion cases whereas the alkali chloride content was reduced.…”
Section: Discussionmentioning
confidence: 99%